2006
DOI: 10.1055/s-2006-926355
|View full text |Cite
|
Sign up to set email alerts
|

A Novel and Efficient Coupling Reaction of Sodium Tetraphenylborate with Hypervalent Iodonium Salts

Abstract: The novel coupling reaction of sodium tetraphenylborate with hypervalent iodonium salts was achieved in acidic water, providing an efficient and rapid method for the formation of carboncarbon bonds in excellent yield.The Suzuki reaction is one of the most versatile and utilized reactions for the selective construction of carboncarbon bonds, in particular for the formation of biaryls. 1 These coupling reactions are utilized extensively in the synthesis of pharmaceuticals, herbicides, and natural products as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…In more recent papers, the electrophilic arylations of sodium arenesulfinates,725 potassium carbonotrithioates,726 and benzazoles727 using diaryliodonium salts in ionic liquids, and the arylations of anilines,728 sodium tetraphenylborate729 and vinylindiums730 have been reported.…”
Section: Iodine(iii) Compoundsmentioning
confidence: 99%
“…In more recent papers, the electrophilic arylations of sodium arenesulfinates,725 potassium carbonotrithioates,726 and benzazoles727 using diaryliodonium salts in ionic liquids, and the arylations of anilines,728 sodium tetraphenylborate729 and vinylindiums730 have been reported.…”
Section: Iodine(iii) Compoundsmentioning
confidence: 99%
“…The same group also reported that similar reactions could be carried out without using either a palladium catalyst or a base. In water, iodonium salts could be coupled either at room temperature under ultrasonic irradiation60 or at 50 °C in acidic conditions 61. Both organic fragments of the iodonium were coupled at 100 °C in water using microwave irradiation 62.…”
Section: Suzuki–miyaura Cross‐coupling With Iodonium Saltsmentioning
confidence: 99%
“…Leadbeater and Marco [12,13] claimed that the Suzuki Miyaura coupling of boronic acids and aryl halides is possible without the need for a transition-metal catalyst ( Table 1, Entry 14-17). In order to investigate the possibility of catalyst-free Suzuki reaction, Yan and his co-workers reported in 2006 a novel and efficient method for coupling reaction of sodium tetraphenylborate with iodonium salts in acidic water [14]. This method was simple, mild, high-yielding, and more environmentally benign ( Furthermore, a class of anionic clay is called layered double hydroxides (LDHs) or hydrotalcite (HTs) has attracted considerable interest from industrial and academic fields.…”
Section: Introductionmentioning
confidence: 99%